Stabilizing lanthanide periodate compounds by slowing periodate reduction at elevated temperatures with NaBiO3, a sacrificial oxidant. (15th July 2021) - Reedy, Colin N.; Villa, Eric M.
Graphical abstract: A family of neodymium periodate, mixed periodate-iodate and iodate compounds have been isolated and characterized from periodic acid flux reactions as a function of time and sodium bismuthate, the latter of which serves as a sacrificial oxidant to inhibit the thermal reduction of periodate at elevated temperatures. Abstract: A series of neodymium periodate, mixed periodate-iodate and iodate structures have been synthesized via periodic acid flux reactions and characterized through single-crystal x-ray diffraction. Critically, the utilization of a sacrificial oxidant, sodium bismuthate (NaBiO3 ), helps to stave off the thermal reduction of periodate. Through the precise control of reaction time and amount of NaBiO3, this facile synthetic technique illuminates new pathways to creating mixed valent iodine compounds and a route to new iodate compounds as well. Herein, we explore the in-situ periodic acid flux redox reactions with neodymium nitrate and sodium bismuthate. The resulting products reveal the evolution of compounds formed as these redox reactions proceed forward with time and presence of NaBiO3 .